Perancangan Pengenalan Profesi untuk Meningkatkan Tingkat Pendidikan Dusun Pucuan Sidoarjo - Masnuna (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2018)
Education is an important means to realize the goals. One of the problems that often happen in the remote areas is education. In remote areas are usually low educational awareness. In the hamlet of Pucuan, Gebang village, Sidoarjo educational level is still very low. Most children in the hamlet of Pucuan education in the level elementary only. To increase the level of education required support of parents and strong motivation from the child itself. Education can be improved in various ways, such as reading. A lots of benefits derived by reading. The design of this social campaign purpose to engage the parents and concerned with elementary school Gebang students for education. In this design using qualitative methods in the form of observation, documentation, and interviews as well as quantitative methods in the form of dissemination the questionnaire. Through the introduction of the professions expected elementary school Gebang are motivated fulfilling their goals by means of continuing education to a higher level. Keywords: Pucuan, Sidoarjo, Social Campaigns, Education, Profession